A study of some molecular addition compounds of zirconium and hafnium tetrahalides. - Chung, F. M. (University of Ottawa (Canada), 1967)
addition complexes MX4-2L, where M is Zr or Hf, x is C1 or Br, and L is tetrahydrofuran or tetrahydrothiophene have been prepared. Thermochemical data have been obtained and the results are interpreted. The enthalpies of reaction of MX(c) - 2L-MX4-2L(c) was measured calorimetrically and the values converted to gas phase and correlated in terms of polarizability and steric effects. The compounds MX4 appear to be on the borderline between class a and class b behavior with hafnium showing a very slightly greater tendency toward class b behaviour. The nuclear magnetic resonance spectra have been obtained for these complexes and the internal chemical shifts determined. The order of the increasing internal shift correlates satisfactorily with the order of internal stability of the complexes. Triphenyl phosphine oxide and triphenyl arsine oxide complexes of zirconium tetrachloride and hafnium tetrachloride have been prepared, they are 1:2 addition complexes except ZrCl4-3Ph3AsO which is a 1:3 addition complex. They are insoluble in common solvents tested, hence neither the thermal measurements nor the n. m. r. spectrometry was carried out. Instead, their infrared spectra were studied with those of corresponding niobium complexes which have also been prepared as 1:2 addition compounds. The analyses of the shifts of the P-O and As-O stretching frequencies confirm the relative hardness of zirconium(IV) chloride and hafnium(IV) chloride as Lewis acids, hence the relative tendency toward class b behaviour thermochemically observed for zirconium and hafnium.
Keywords: Chemistry, Inorganic.